Correlation Between MRI and Pathology in Rectal Cancer - Freire, Ana Carolina Sampaio; Testi, Isabela Augusta Carvalho; Braga, Ana Carla Franklin; Filho, Oswaldo de Moraes; Soares, Mayra Veloso Ayrimoraes; Almeida, Romulo Medeiros de; Alves Martins, Bruno Augusto; Sousa, João Batista de (Journal of Coloproctology, 2025)
Colorectal cancer is the third leading cause of cancer-related mortality in Brazil. Proper staging is crucial for the management of patients with rectal cancer, as the implemented therapies may result in implications for the prognosis and quality of life. The therapeutic armamentarium has evolved over time, highlighting the importance of magnetic resonance imaging (MRI) in preoperative evaluation. This study aims to assess the correlation between clinical staging by MRI and pathological staging in individuals with rectal cancer.Cross-sectional observational study in patients diagnosed with rectal cancer from the Colorectal Surgery Department at the University Hospital of Brasília. Demographic data and clinical and pathological staging were analyzed. The degree of agreement and reliability between the clinical and pathological staging results was assessed by the Kappa (k) and weighted Kappa (wk) tests.Seventy-six patients were studied. Fair agreement was observed for T staging between clinical T and pathological T, being stronger for T3. In patients who underwent neoadjuvant therapy prior to surgery, the reliability was slight, while without neoadjuvant therapy, it was moderate. There was slight agreement between clinical and pathological stages for N staging, which was more substantial in patients without neoadjuvant therapy.This study highlights the importance of MRI in the preoperative staging of rectal cancer but emphasizes the need to consider other aspects before defining the treatment plan.
Keywords: Rectal Cancer; TNM staging; MRI scan